2019
DOI: 10.2298/fil1912901c
|View full text |Cite
|
Sign up to set email alerts
|

On a projective conformal semi-symmetric connection

Abstract: In this paper we propose a projective conformal semi-symmetric connection and study its geometric and physical properties. The Schur's theorem of this connection is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Based on relations (4.9) and (4.14), we conclude that curvature tensor ∇ is conjugate symmetric (see [5]). From here we see that the connection Remark 4.1 In paper [24], the authors observed quarter-symmetric non-metric connection in the form…”
Section: Properties Of Curvature Tensorsmentioning
confidence: 75%
See 1 more Smart Citation
“…Based on relations (4.9) and (4.14), we conclude that curvature tensor ∇ is conjugate symmetric (see [5]). From here we see that the connection Remark 4.1 In paper [24], the authors observed quarter-symmetric non-metric connection in the form…”
Section: Properties Of Curvature Tensorsmentioning
confidence: 75%
“…This connection was also studied in papers [4,5]. These papers motivated us to study the quarter-symmetric connection on the generalized Riemannian manifold in the following form…”
Section: Introductionmentioning
confidence: 99%
“…Some other geometric object can be defined using curvature tensor, for example Ricci curvature tensor, scalar curvature, Weyl tensor, etc. In the articles [2,3,20], the curvature tensor was studied at various mappings and transformations (see also the monographs [4] and [7]).…”
Section: Introductionmentioning
confidence: 99%